Benefits of a Supervised Ambulatory Outpatient Program in a Cardiovascular Rehabilitation Unit Prior to a Heart Transplant: A Case Study - Poty, Antoine; Krim, Florent; Lopes, Philippe; Garaud, Yves; Leprêtre, Pierre-Marie (Frontiers in Cardiovascular Medicine, 2022)
Preoperative peak oxygen uptake (V ̇O2peak) and ventilatory efficiency (V ̇E/V ̇CO2 slope) are related to the vital prognosis after cardiac transplantation (HTx). The objective of our study was to evaluate the effects of exercise-based cardiac rehabilitation program (ECR) on the preoperative exercise capacity of a HTx candidate. A male patient, aged 50 to 55 years, with chronic heart failure placed on HTx list, performed 12 weeks of intensive ECR (5 sessions-a-week). Our results showed that the cardiac index continuously increased between the onset and the end of ECR (1.40 vs. 2.53 L.min-1.m2). The first 20 sessions of ECR induced a V ̇O2peak increase (15.0 vs. 19.3 mL.min-1.kg-1, corresponding to 42.0 and 53.0% of its maximal predicted values respectively). The peak V ̇O2 plateaued between the 20th and the 40th ECR session (19.3 vs. 19.4 mL.min-1.kg-1) then progressively increased until the 60th ECR session to reach 25.7 mL.min-1.kg-1, i.e 71.0% of the maximal predicted values. The slope of V ̇E/V ̇CO2 showed a biphasic response during ECR program, with an increase between the onset and the 20th ECR session (58.02 vs. 70.48) and a decrease between the 20th and the 40th ECR session (70.48 vs. 40.94) to reach its minimal value at the 60th ECR session (31.97). After the first 40 sessions of ECR program, the Seattle Heart Failure Model score predicted median survival time was estimated at 7.2 years. In conclusion, the improvement in exercise capacity and cardiorespiratory function following the exercise-based cardiac rehabilitation helped delaying the heart transplant surgery in our patient awaiting heart transplantation.